Músicos de pop-rock: queixas auditivas e não auditivas decorrentes da exposição à música eletronicamente amplificada - Salgado, Joana D'Arc Aparecida (2012)
Introduction: The musicians are part of a professional category under the risk of auditory issues and health complaints, due to electronically amplified music exposure. Objective: Measuring sound levels and identifying auditory and non-auditory complaints on pop-rock musicians groups. Method: 34 male pop-rock musicians, ages between 26 and 60 years old were evaluated. The subjects answered a questionnaire composed of health history, complaints related to hearing and information about music exposure. The noise dosimeter was applied on the musicians during a band concert on a nightclub in São Paulo. It was used a dosimeter type 1, properly calibrated, in which the microphone was positioned behind the musician s ear, 5 minutes before the beginning of the presentation. Results: The prevalence of auditory complaints, loud sound intolerance and the felling of occluded ears was 20,6%. From all, 50% of the sample reported the thought of being exposure to that sound can damage their hearing. The majority (27, 79,4%) of the musicians work in this area for further than 10 years. The highest sound level obtained on Lmax variation medium maximum levels, Lavg - average levels and Lmin - medium minimum levels in dB (A) were of 129,6; 119,1 and 94,5 (respectively). The values were further above the maximum level daily allowed, according to the occupational legislation. Conclusions: Dosimeter can be useful on levels investigation. Although, measures for musicians protection must be immediately taken, so that it can avoid deleterious effects on this population health